Show last authors
1 {{formula}}
2 F^{\mu\nu} = \partial^\mu A^\nu - \partial^\nu A^\mu
3 {{/formula}}
4
5 {{formula}}
6 A_\mu F^{\mu\nu} = A_\mu\partial^\mu A^\nu - A_\mu\partial^\nu A^\mu
7 {{/formula}}
8
9 {{formula}}
10 A_0 F^{00} = \varphi\frac{\partial \varphi}{\partial t}-\varphi\frac{\partial \varphi}{\partial t}
11 {{/formula}}
12
13 {{formula}}
14 A_0 F^{01} = \varphi\frac{\partial A_x}{\partial t} - \varphi \frac{\partial \rho}{\partial x}
15 {{/formula}}
16
17 {{formula}}
18 -\varphi\frac{\partial A}{\partial t} - \varphi \nabla \varphi = \varphi E
19 {{/formula}}
20
21 {{formula}}
22 A_1 F^{00} = A_x\frac{\partial \varphi}{\partial x}-A_x\frac{\partial A_x}{\partial t}
23 {{/formula}}
24
25 {{formula}}
26 A\nabla \varphi + A \frac{\partial A}{\partial t}
27 {{/formula}}
28
29 {{formula}}
30 \nabla \cdot (\varphi A) - \varphi (\nabla \cdot A) + \frac{1}{2}\frac{\partial A \cdot A}{\partial t} = 0
31 {{/formula}}
32
33 {{formula}}
34 \nabla \cdot (\varphi A) + \frac{1}{2}\frac{\varphi \varphi}{\partial t} + \frac{1}{2}\frac{\partial A \cdot A}{\partial t} = 0
35 {{/formula}}
36
37 {{formula}}
38 \nabla \cdot A = -\frac{1}{2}\frac{1}{\varphi}\frac{\partial A \cdot A}{\partial t}
39 {{/formula}}
40